HIGH ARSENIC CONCENTRATION IN GROUNDWATER RELATED TO SEDIMENTARY FACIES IN THE MEKONG RIVER DELTA, VIETNAM - Oanh*, Ta Thi Kim; Lap, Nguyen Van (Vietnam Journal of Earth Sciences, 2016)
Arsenic (As) contamination in groundwater has been recognized in the Mekong River Delta (MRD) since 2001, especially in Dong Thap and An Giang provinces. The investigations were carried out during 2008-2009 and from 2012 to present. The investigations of As distribution in groundwater and sediments were based upon the field, and laboratory analyses using field kit (Hironaka, 1998) and AOAC laboratory - Vietnamese standard 6626-2000 (Vilas). Results show that the As concentrations ranging from 15 to 1,650 µg/l is found in 520 private tubewells at depth between 15 and 90 m, while being rare or very low at depth between 200 and 300 m. High As content is usually found in 15-70m tubewells in which approximately 70 - 80% of tubewells having arsenic levels of >500µg/l are located at some areas in Dong Thap and An Giang provinces in the upper MRD plain. Bore core drilling records show a probable relationship between As concentration in groundwater and sedimentary facies in the MRD. The highest As content is found along the Mekong River valleys in the Late Pleistocene and Holocene aquifers. References Ahmed, K.M., et al., 2004. Arsenic enrichment in groundwater of the alluvial aquifers in Bangladesh: an overview, Applied Geochemistry, 19(2), 181-200. Nguyen. V.L., Ta. T.K.O., Tateishi. M., 2000. Late Holocene depositional environments and coastal evolution of the Mekong River Delta, Southern Vietnam. Journal of Asian Earth Sciences. 18(4), 427-439. Nguyen. V.L., Ta. T.K.O., and Nguyen. V.D., 2006. Some results from study on arsenic contamination in groundwater in the Mekong River Delta and solutions to prevent. VAST Workshop on Science and Technology in relation of practice. Ho Chi Minh City. 6 pp. (in Vietnamese with English abstract). Nguyen, V.L., Ta. T.K.O., and Nguyen. V.D., 2008: Groundwater arsenic contamination in the Mekong River Delta - its effect on environment and public health. Proceedings of Research on Science and Technology, HCMC Institute of Resources Geology, 47-53 (in Vietnamese with English abstract). Nguyen. V.L., Ta. T.K.O. and Nguyen. V.D., 2009: Recent situation of arsenic contamination in groundwater in Dong Thap Province, Mekong River Delta, Southern Vietnam. Technical report. 98 pp (in Vietnamese). Nguyen Van Lap, Ta Thi Kim Oanh, Saito, Y., 2010: Early Holocene initiation of the Mekong River Delta, Vietnam, and the response to Holocene sea-level changes detected from DT1 core analyses. Sedimentary Geology, 230, 146- 155. Polizzotto, M.L., Kocar B.D., Benner, S.G., Sampson, M. and Fendorf, S., 2008: Near-surface wetland sediments as a source of arsenic release to ground water in Asia. Nature 454, 505-508. Ta, T.K.O., Nguyen, V.L., Tateishi, M., Iwao, K., Saito, Y., 2002: Holocene delta evolution and sediment discharge of the Mekong River, southern Vietnam. Quaternary Science Reviews, 21, 1807-1819. Ta. T.K.O., Nguyen. V.L., Tateishi. M., Kobayashi. I., Saito. Y., 2005: Holocene delta evolution and depositional models of the Mekong River Delta, southern Vietnam. In L. Giosan and J.P. Bhattacharya. eds., River Deltas-Concepts, Models and Examples. SEPM special publication. 83. 453-466. Tamura T., Saito Y., Sieng, S., Ben, B., Kong, M., Choup, S., Tsukawaki, S., 2009. Initiation of the Mekong River delta at 8 ka: evidence from the sedimentary succession in the Cambodian lowlands. Quaternary Science Reviews 28, 327-344. Research Group for Applied Geology, 1999: Arsenic contamination of groundwater in Bangladesh, Tech. Rep., 90.